2015
DOI: 10.1093/mnras/stv337
|View full text |Cite
|
Sign up to set email alerts
|

The response of a helium white dwarf to an exploding Type Ia supernova

Abstract: We conduct numerical simulations of the interacting ejecta from an exploding CO white dwarf (WD) with a He WD donor in the double-detonation scenario for Type Ia supernovae (SNe Ia), and study the possibility of exploding the companion WD. We also study the long time imprint of the collision on the supernova remnant. When the donor He WD has a low mass, M WD = 0.2M ⊙ , it is at a distance of ∼ 0.08R ⊙ from the explosion, and helium is not ignited. The low mass He WD casts an 'ejecta shadow' behind it. By evolv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…The SN ejecta collides with the companion WD, and the interaction of the SN ejecta with the companion WD form the ejecta shadow and companion-origin stream. Papish et al (2015) have also found out such ejecta shadows in their simulations for their D 6 models. The companion WD survives the explosion of the primary WD, and flies away at velocity of ∼ 1700 km s −1 as the surviving WD.…”
Section: Discussionmentioning
confidence: 74%
“…The SN ejecta collides with the companion WD, and the interaction of the SN ejecta with the companion WD form the ejecta shadow and companion-origin stream. Papish et al (2015) have also found out such ejecta shadows in their simulations for their D 6 models. The companion WD survives the explosion of the primary WD, and flies away at velocity of ∼ 1700 km s −1 as the surviving WD.…”
Section: Discussionmentioning
confidence: 74%
“…(1) If the explosion of the two WDs in the DD scenario occurs as they dynamically interact, then the explosion is asymmetrical (e.g., Kashyap et al 2017;Pakmor et al 2012;Tanikawa et al 2015;van Rossum et al 2016), contradicting the structure of most SN Ia remnants (SNRs Ia) that tend to be spherical or axisymmetrical (e.g., Lopez et al 2011). In that respect I note that a surviving WD companion in the DDet scenario also leads to a SNR Ia that possesses non-spherical morphological features (e.g., Papish et al 2015).…”
Section: Merger To Explosion Delay (Med) Timementioning
confidence: 99%
“…Papish et al (2015) list two problems with the SES scenario. When confronting the scenarios with observations, as well as when trying to account for a specific observational property, it is imperative to consider all scenarios.…”
Section: Introductionmentioning
confidence: 99%